Advances and prospects in the development of GdVO4-based photocatalysts for water pollutants removal activity: A review - Selvaraj Mohana Roopan; Thangapandi Chellapandi; Roshan Mohammed Shebeer; E. Akhil; Jerry D. Alappat; Nived Rajeshkumar Nair; Manasa Madhusoodanan; D. Chitra (Nano Materials Science)
Human society is currently facing significant and pressing issues in the form of serious environmental pollution and energy shortages, which have arisen owing to the rapid development of the economy and contemporary industry. Photocatalysis has considerable potential as a viable technique for providing sustainable and environmentally friendly energy sources. The use of lanthanide-based photocatalysts on supporting substrates has garnered significant attention over the past decade within the scope of organic pollution remediation. Owing to its unique and promising bandgap, electrical conductivity, and stability, traditional GdVO4 exhibits remarkable photocatalytic performance with ongoing advances and advancements. This review provides an overview of the latest advancements in the modification techniques employed for GdVO4-based photocatalysts, with a specific focus on their application in the photocatalytic degradation of organic pollutants. The supplied information provides a concise overview of current obstacles, limitations, advancements, mechanisms, and potential prospects for new opportunities. This review is anticipated to provide a significant reference and scientific justification for the active development of GdVO4-based materials for environmental applications.